Research progress on perioperative blood-brain barrier damage and its potential mechanism - Qiu, Yong; Mo, Chunheng; Xu, Shiyu; Chen, Lu; Ye, Wanlin; Kang, Yi; Chen, Guo; Zhu, Tao (Frontiers in Cell and Developmental Biology, 2023)
The blood-brain barrier (BBB) is an important barrier separating the central nervous system from the periphery. The composition includes endothelial cells, pericytes, astrocytes, synapses and tight junction proteins. During the perioperative period, anesthesia and surgical operations are also a kind of stress to the body, which may be accompanied by BBB damage and brain metabolism dysfunction. Perioperative BBB destruction is closely associated with cognitive impairment and may increase the risk of postoperative mortality, which is not conducive to enhanced recovery after surgery. However, the potential pathophysiological process and specific mechanism of BBB damage during the perioperative period have not been fully elucidated. Changes in BBB permeability, inflammation and neuroinflammation, oxidative stress, ferroptosis, and intestinal dysbiosis may be involved in BBB damage. We aim to review the research progress of perioperative BBB damage and its potential adverse effects and potential molecular mechanisms, and provide ideas for the study of homeostasis maintenance of brain function and precision anesthesia.